2022
DOI: 10.1016/j.immuni.2021.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Germline HLA landscape does not predict efficacy of pembrolizumab monotherapy across solid tumor types

Abstract: Highlights d >3,500 solid tumor samples from 17 pembrolizumab trials (8 tumor types) were analyzed d HLA diversity across class I loci was not associated with improved responses d HLA heterozygosity at each class I/class II gene was not associated with response d Germline HLA genotype or diversity alone is not a determinant of pembro response

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Such pretreatment biomarkers can help inform clinical judgment and lead to better outcomes by identifying progression events sooner, limiting usage of ineffective and costly ICB regimens, and improving patient quality of life by potentially transitioning to the next line of therapy before asymptomatic progression becomes symptomatic progression. We note that biomarkers considering HLA-LOH and HLA diversity alone have produced contradictory results in predicting ICB outcomes 9,14,15,69 . Such HLA-I deficiencies are thought to limit tumor antigen presentation to CD8 + T cells but do not account for the potential role of cytotoxic CD4 + T cells.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Such pretreatment biomarkers can help inform clinical judgment and lead to better outcomes by identifying progression events sooner, limiting usage of ineffective and costly ICB regimens, and improving patient quality of life by potentially transitioning to the next line of therapy before asymptomatic progression becomes symptomatic progression. We note that biomarkers considering HLA-LOH and HLA diversity alone have produced contradictory results in predicting ICB outcomes 9,14,15,69 . Such HLA-I deficiencies are thought to limit tumor antigen presentation to CD8 + T cells but do not account for the potential role of cytotoxic CD4 + T cells.…”
Section: Discussionmentioning
confidence: 84%
“…Leiden clustering was performed using Scanpy with a resolution of 0.7 for the CD8 cells and 0.8 for the CD4 cells. Cell cycle status was assessed using the score_genes_cell_cycle function in Scanpy with the gene list from Tirosh et al 69 PAGA graphs were generated with the paga function in Scanpy with 6 neighbors and the first 20 principal components. Differential expression analysis was performed using the rank_genes_groups function in Scanpy with the Wilcoxon Rank-Sum test.…”
Section: Methodsmentioning
confidence: 99%
“…ICI specificity) by finding no difference in OS for non‐ICI‐treated patients. However, these findings were not replicated in another recent pan‐cancer analysis of pembrolizumab (anti‐PD1)‐treated patients; thus, its clinical use remains investigational [45].…”
Section: Germline Genetic Featuresmentioning
confidence: 99%
“…They found that greater mean HED was associated with better OS and ORR in melanoma and NSCLC patients, consistent with the ‘divergent allele advantage’ theory (whereby more diverse HLA‐I allele pairs would plausibly present more diverse cancer neoantigens). However, the relationship of HLA‐I zygosity and/or mean HED and better ICI efficacy has not been consistently found in more recent analyses for non‐melanoma cohorts [45,49–51]. Importantly, the HLA‐B44 supertype seemed to impart an opposite, negative effect in NSCLC, potentially due to NSCLC's distinct neoantigen landscape (leading to worse presentation on HLA‐B44 ) [52].…”
Section: Germline Genetic Featuresmentioning
confidence: 99%
“…In a meta-analysis of factors that influence ICI efficacy, Litchfield et al also showed that HLA divergence was a significant factor influencing ICI response in melanoma ( 64 ). If HLAs are not actually typed but are estimated by imputation using microarrays, associations may be not apparent ( 99 ). Based on more recent modeling data, it appears that HED has a somewhat weaker effect compared with TMB, treatment beforehand with chemotherapy, or neutrophil/lymphocyte ratio.…”
Section: Tumor Cell–extrinsic Determinants Of Responsementioning
confidence: 99%